O papel das tecnologias da informação e comunicação na educação corporativa - Cuogo, Francisco Coelho (2014)
This dissertation aims to examine the role of information and communication technologies in corporate education, in the context of the information society. The problem of this research demonstrates the use of information and communication technologies in education, especially the online education and its methods, reflecting the use of information and communication technologies in corporate education. The corporate education, inserted in contemporary organizations that develop education programs for its employees has been making use of the tools and methods also used in distance education. Thus, we consider in this paper the characteristics of the industrial age, the mechanical work and the informational society, considering its consequences for education. To write about the information society, making considerations about cyberspace and the concept of networks, concepts of Castells (2002), Lévy (1999) and Lemos (2002) were analyzed. The aspects related to education, addressing the perspectives of the industrial society, the information society and in distance education, use Aranha (2006), Moran (2011) and Maia & Mattar (2007). On corporate education we base the theoretical approach in Eboli (2004), Meister (1999) and Milkovich & Boudreau (2008). The research has raised qualitative data through questionnaires applied to a group of four professionals responsible for corporate education in their respective companies. For analysis of the questionnaires was considered the method of textual analysis of Bardin (1994). From our analysis we conclude that there is a gap between the theoretical approaches to the corporate education and understanding on the subject in the surveyed organizations, as well as a distortion in relation to what is developed in practice in terms of CE. Still showing an underutilization of the potential of information and communication technologies in corporate education, whose focus seems to be geared more to achieve the interests of organizations rather than the proposed development of employees.